Threat simulation in virtual limbo: An evolutionary approach to horror video games. Issue 2 (1st September 2019) - Kjeldgaard-Christiansen, Jens; Clasen, Mathias
Why would anyone want to play a game designed to scare them? We argue that an alliance between evolutionary theory and game studies can shed light on the forms and psychological functions of horror video games. Horror games invite players to simulate prototypical fear scenarios of uncertainty and danger. These scenarios challenge players to adaptively assess and negotiate their dangers. While horror games thereby instil negative emotion, they also entice players with stimulating challenges of fearful coping. Players who brave these challenges expand their emotional and behavioural repertoire and experience a sense of mastery, explaining the genre's paradoxical appeal. We end by illustrating our evolutionary approach through an in-depth analysis of Playdead's puzzle-horror game Limbo.